The effect of local ketamine infiltration on post tonsillectomy pain scale - Ade Asyari; Novialdi Novialdi; Elniza Morina; Rimelda Aquinas; Nasman Puar; Hafni Bachtiar (Oto Rhino Laryngologica Indonesiana, 2020)
Background: Post tonsillectomy pain is one of the surgery side effects that most disturbing for patient’s comfort and will cause dysphagia, low intake, dehydration, secondary infection and bleeding. Ketamine is an anesthetic drug that has strong analgesic effect and easily available in any hospital at relatively cheap price. Objective: To find out the effect of local ketamine infiltration on the post tonsillectomy pain scale. Method: An experimental study during tonsillectomy with a Post Test Control Group on 12 samples without local infiltration of ketamine and 12 samples with local infiltration of ketamine in peritonsillar pillar. The pain was assessed 2 hours and 24 hours post extubation with pain Visual Analog Scale (VAS). Result: The VAS value from patients who were given local infiltration of ketamine in peritonsillar pillar were lower (5.83 ± 0.72 at 2 hours and 2.83 ± 0.58 at 24 hours post extubation) compared to patients without ketamine infiltration (7.83 ± 0.58 at 2 hours and 3.58 ± 0.51 at 24 hours post extubation). The result showed statistically significant difference (p <0.05) at 2 hours and 24 hours post extubation. Conclusion: The VAS score of the ketamine infiltration group is lower at 2 hours and 24 hours post extubation than the group without ketamine infiltration, showing there was a noticeable effect of local ketamine infiltration on the post tonsillectomy pain scale.Keywords : post tonsillectomy pain, ketamine, local infiltration, visual analog scale ABSTRAKLatar belakang: Nyeri pascatonsilektomi adalah salah satu efek samping operasi yang sangat mengganggu kenyamanan pasien, dan dapat menyebabkan gangguan menelan, kurangnya asupan nutrisi, dehidrasi, infeksi sekunder dan perdarahan. Ketamin merupakan obat anestesi yang memiliki efek analgetik yang kuat dan mudah didapatkan di semua tipe rumah sakit dengan harga yang relatif murah. Tujuan: Mengetahui efek pemberian infiltrasi lokal ketamin terhadap skala nyeri pascatonsilektomi. Metode: Penelitian eksperimental dengan desain Post Test Control Group pada 12 sampel tanpa pemberian infiltrasi lokal ketamin dan 12 sampel dengan pemberian infiltrasi lokal ketamin di pilar peritonsil saat tonsilektomi. Dilakukan penilaian nyeri 2 jam dan 24 jam pascaekstubasi menggunakan skala nyeri Visual Analog Scale (VAS). Hasil: Nilai VAS pasien yang diberi infiltrasi lokal ketamin di pilar peritonsil lebih rendah (5,83±0,72 pada 2 jam dan 2,83 ± 0,58 pada 24 jam pascaekstubasi) dibanding tanpa diberi infiltrasi lokal ketamine (7,83 ± 0,58 pada 2 jam dan 3,58± 0,51 pada 24 jam pascaekstubasi), dan bermakna secara statistik (p<0,05) pada kedua penilaian. Kesimpulan: Terdapat efek nyata infiltrasi lokal ketamin terhadap skala nyeri pascatonsilektomi, dimana nilai VAS kelompok yang diberi infiltrasi ketamin lebih rendah, baik pada 2 jam ataupun 24 jam pascaekstubasi dibanding kelompok yang tidak diberi infiltrasi ketamin.